P-Cresol mediates autophagic cell death in renal proximal tubular cells. Issue 1 (2nd April 2015) - Lin, Hsin-Hung; Huang, Chiu-Ching; Lin, Tze-Yi; Lin, Ching-Yuang
Highlights p-Cresol (PC), a uremic toxin, decreases proliferation of renal proximal tubular cells (RPTC). PC induces autophagy in RPTC through c-Jun activation mediated p62 accumulation. PC promotes autophagic cell death in RPTC via caspase 8, followed by caspase 3 activation, which participates significantly to cell apoptosis.